The man who shot Liberty Valance - Goldbeck, Willis; Ford, John (Paramount Pictures, 1962)
Jimmy Stewart, plays the bungling but charming big-city lawyer determined to rid the fair village of Shinbone of its number one nuisance and bad man: Liberty Valance. And as if all that weren't enough, the biggest star that ever aimed a six-shooter plays the man of the title.